Coparenting, Negative Educational Outcomes, and Familial Instability in Justice-involved Families - Tadros, Eman (International journal of offender therapy and comparative criminology, 2022)
Incarceration of a parent is associated with negative consequences for children, such as behavioral problems, the development of antisocial personality traits, and decreased educational attainment. Data from the Multi-site Family Study on Incarceration, Parenting, and Partnering was used to analyze four measures of the coparenting relationship in families in which the father is incarcerated and the mother is not, to examine if a higher quality, more cohesive coparenting relationship is associated with fewer adverse childhood experiences for the parents’ shared child. Findings suggest that children of parents who frequently argue about the child are more likely to have ever been suspended or expelled from school and are more likely to have ever had to live outside of the home with a relative, family friend, or foster parents. Clinical implications are discussed, and future directions call for research, practice, and training to improve outcomes for incarcerated coparents and their children.